Sistem Pendukung Keputusan Pemilihan Sepeda Motor Bekas Dengan WASPAS - Fauzan Meganuari; TH Dwiati Wismarini (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
Most people who want to find a used motorcycle will first seek information about the price of a used motorcycle through the internet or newspapers. This is less effective because it will waste a lot of time and money, especially if you have to look for information on used motorcycles one by one but the results are not in accordance with your wishes and needs. To facilitate the search for used motorcycles, the WASPAS method is used. Attributes of used motorcycles include: brand, transmission, model, type, price, cc, year of manufacture. Used motorcycles are recommended only for three well-known brands, namely Yamaha, Honda and Suzuki with the WASPAS method. This study aims to build a decision support system that can be used to provide recommendations for the selection of used motorcycles according to the wishes and needs of consumers using the WASPAS method. The used motorcycle selection system using the WASPAS method with the selection of criteria for used motorcycles by choosing the Honda brand and automatic transmission, the results obtained are Honda Scoopy recommendations with a value of 1.00.